PERSEPSI TOKOH GERAKAN ACEH MERDEKA TERHADAP PEMIKIRAN TEUNGKU HASAN TIRO TAHUN 1976-2005 - Fajri, Heri; Muliana, Muliana; Zaini, Muhammad (Universitas Jabal Ghafur, 2024)
This study aims to (1) analyze the ideology developed by Teungku Hasan Tiro in establishing the Free Aceh Movement, (2) analyze the thoughts developed by Teungku Hasan Tiro, (3) analyze the perception of the Free Aceh Movement figures towards Teungku Hasan Tiro's Thoughts. This type of research is descriptive qualitative research, the data collection method is carried out by means of observation, namely, literature studies and documentation related to the Free Aceh Movement Figures, Teungku Hasan Tiro's thoughts. The results of this study indicate that (1) The ideology taught by Teungku Hasan Tiro is an ideology based on a scientific foundation, namely historical facts and international law. which is solid and can be accepted by the international community in general. the ideology is formulated into a tool of struggle, namely the Free Aceh Movement (GAM). (2) The aspect of thought developed by Teungku Hasan Tiro is to offer the concept of a federal state to the Indonesian government, according to him, Soekarno's concept of democracy is primitive because it does not respect national rights, the rights of regional diversity in Indonesia, the concept is rejected and shifts to the concept of Acehnese nationalism. (3) The perception of the Free Aceh Movement (GAM) figures regarding Teungku Hasan Tiro's thoughts is about the Free Aceh ideology that he built based on historical facts and international law. Hasan Tiro's ideology places the Acehnese Islamic community as a 'historical fact' or a reality that lives in society. Keywords: Free Aceh Movement, Hasan Tiro, perception